3rd European Quality of Life Survey Quality of life in Europe : Quality of society and public services - Gstrein, Michaela; Mateeva, Liliana; Rodiga-Labnig, Petra; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2012)
Quality of life depends on individual circumstances and on the quality of the society at large; this is in turn partly shaped by the availability of good-quality public services. Services such as health, education and social care enable citizens to lead fulfilling lives. The quality of society is also shaped by social relationships and how well they function: conflict or inequality between social groups, or a lack of trust between people, can affect everybody's well-being. This report is based on the 2011 European Quality of Life Survey conducted by the European Foundation for the Improvement of Living and Working Conditions (Eurofound), the third such survey. The global economic crisis, which began after the last survey was carried out in 2007, has meant that public services have been threatened, inequalities have increased and unemployment has risen, with potentially profound implications for the quality of life in Europe.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Social well-being -- European Union countries; Living conditions -- European Union countries; Social surveys -- European Union countries; Electronic books